The impacts of perceived overqualification on employee performance: A case of chefs - Gökhan ONAT; Duygu Eren (Tourism & Management Studies)
There are many variables that affect employee performance in working life. Some of these variables originate from individuals, while others are caused by external factors. One of the individual factors that affects employee performance is perceived overqualification. In this research, the effect of perceived overqualification in the hospitality industry on employee performance is discussed. Research data were collected through a questionnaire form. The data of the current study, which utilized 138 usable questionnaires, were collected from the kitchen staff of 4- and 5-star hotels in Nev?ehir. A road analysis test was used to test the hypothesis of the research. As a result of the analysis made with the data collected, it was found that perceived overqualification negatively and significantly affects employee performance. In this context, as a result of this study, it can be said that employee performance may increase or decrease if the overqualification observed in chefs increases or decreases. In light of the results obtained as a result of the study, practical implications and suggestions have been made for future studies.